If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 1 + 2x + 1 Reorder the terms: -6 = 1 + 1 + 2x Combine like terms: 1 + 1 = 2 -6 = 2 + 2x Solving -6 = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + -2x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -2x = 2 + 0 -6 + -2x = 2 Add '6' to each side of the equation. -6 + 6 + -2x = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 2 + 6 -2x = 2 + 6 Combine like terms: 2 + 6 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| 4x-3-2x=35 | | 234-6x=18 | | y=100+200(2) | | 87=7+5r | | 40+15+.25m=45+.10m | | 2x+5x-15=-8+4x+9 | | Sqrtx^2-3x=2 | | 4x+1=36-X | | 8b+6=36 | | 50=4.25x+80 | | 7+r=7(1+8r) | | y=100+200x | | 4(2m+3)-15=-19 | | y=4x+8r | | (-6)(-0.002)= | | -3y-11=2y+14 | | 2v-8(v-7)=32+2v | | -24-x=-19 | | 14.43+0.12h=15.18-0.08h | | 2x+28+10=27+x | | -4(1+3v)=-16 | | 22v-8(v-7)=32+2v | | 5(y-2)+8y= | | 100c=1+5c | | (6w^2+5w-7)(3w-4)= | | =x+0.07 | | 7x+7=-4+5x+15 | | 4x-4-5x=-2 | | F(x)=6-4x | | 12(x+3)=4(2x+9)4x | | 122=x-8(1-8x) | | 5(-2x+9)=45 |